An evaluation of tuberculosis surveillance system in a health district in Ghana - Mohammed, Naziru T.; Bawa, Salifu; Adgei, Michael R.; Appiah, Paulina; Gladzah, Annick; Barima, Moses D.; Yawson, Alfred E. (International Journal Of Community Medicine And Public Health, 2020)
Background: Tuberculosis remains a major global health problem. It is one of the top 10 causes of death worldwide. In Africa, there were estimated 2.7 million new cases of tuberculosis and 450 thousand deaths in 2014. In Ghana, incidence rate of TB was estimated to be 152 per 100,000 populations in 2017 according to the WHO estimates. We evaluated a health district (Ejisu-Juaben) Tuberculosis surveillance system to describe its operations, attributes, determine its usefulness and whether its objectives were being met. Methods: This descriptive study was conducted using the Center for Disease Control and Prevention updated guidelines for evaluating public health surveillance systems and the Ghana Health Service Standard Operating Procedures for priority diseases and conditions (2012). Study participants who were purposively sampled were interviewed with a semi-structured questionnaires and dataset from January 2016 to December 2018 were reviewed at various levels of the surveillance system. Data was collected and analyzed with Epi Info 7.2 between 1st February, 2019 and 30th April, 2019. Results: The surveillance system was useful and partially met its objectives and targets. It was well structured, simple, stable, flexible and of good data quality. It was also averagely acceptable and representative. However, it recorded poor sensitivity of 15.12% and poor predictive value positive (PVP) of 12.27% in 2018. The yearly total cost of operation of the TB surveillance system was ¢79,950.76 ($16,316.44 USD). Conclusions:The surveillance system was useful and met its objectives partially. The sensitivity, PVP, acceptability and representativeness need improvement in order to justify its relevance.